2014
DOI: 10.1158/1078-0432.ccr-14-1397
|View full text |Cite
|
Sign up to set email alerts
|

Ponatinib Inhibits Polyclonal Drug-Resistant KIT Oncoproteins and Shows Therapeutic Potential in Heavily Pretreated Gastrointestinal Stromal Tumor (GIST) Patients

Abstract: Purpose KIT is the major oncogenic driver of gastrointestinal stromal tumors (GISTs). Imatinib, sunitinib and regorafenib are approved therapies; however, efficacy is often limited by the acquisition of polyclonal secondary resistance mutations in KIT, with those located in the activation (A) loop (exons 17/18) being particularly problematic. Here we explored the KIT inhibitory activity of ponatinib in preclinical models and describe initial characterization of its activity in GIST patients. Experimental Des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(150 citation statements)
references
References 34 publications
6
143
0
1
Order By: Relevance
“…Regorafenib ist ein Multikinaseinhibitor von Proteinkinasen, die an Tumorangiogenese (VEGFR-1, -2, and -3, and TIE2), Onkogenese (KIT, RET, RAF-1, BRAF, und BRAFV600E) und dem Tumormikroenvironment (PDGFR und FGFR) beteiligt sind [52]. [54].…”
Section: Kongressbericht 239unclassified
“…Regorafenib ist ein Multikinaseinhibitor von Proteinkinasen, die an Tumorangiogenese (VEGFR-1, -2, and -3, and TIE2), Onkogenese (KIT, RET, RAF-1, BRAF, und BRAFV600E) und dem Tumormikroenvironment (PDGFR und FGFR) beteiligt sind [52]. [54].…”
Section: Kongressbericht 239unclassified
“…It was shown to significantly inhibit tumor growth in in vitro and in vivo models of glioblastoma multiforme [73] and acute myeloid leukemia [74]. To elucidate the in vitro and in vivo efficacy of ponatinib, Garner and colleagues assessed the drug across a panel of GIST cell lines derived from patients with varying mutational statuses [75]. They demonstrated that ponatinib was highly active in lines containing KIT exon 11 mutation and an array of secondary mutations, including activation loop and T670I gatekeeper mutations, but not V654A secondary mutation.…”
Section: Kit and Pdgfra Inhibitorsmentioning
confidence: 99%
“…Among novel multikinase inhibitors, ponatinib might have the potential to become a new treatment option for patients refractory to all known TKIs. Ponatinib has demonstrated in vitro activity against a number of clinically relevant KIT mutants [88]. In a phase II study of 35 patients with refractory metastatic GISTs, roughly 50% of whom had progressed on all three established TKIs, ponatinib achieved response or disease stabilization in 55% of patients with and 22% of patients without a primary KIT exon 11 mutation [89].…”
Section: Management Of Advanced/metastatic Gistsmentioning
confidence: 99%